Finishing Global Farm Trade Reform: implications for developing countries - Anderson, Kym (University of Adelaide Press, 2016)
This study reviews policy developments in recent years and, in the light of that, explores ways in which further consensus might be reached among WTO members to reduce farm trade distortions - and thereby also progress the multilateral trade reform agenda. Particular attention is given to ways that would boost well-being in developing countries, especially for those food-insecure households still suffering from poverty and hunger.